2019
DOI: 10.1371/journal.pone.0214114
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-methods study of women’s sanitation utilization in informal settlements in Kenya

Abstract: While access to safe sanitation is a global issue, there are large disparities in access. Women living in informal settlements, in particular, are disproportionately affected by lack of access to sanitation. Without adequate sanitation, these women may resort to unsafe strategies to manage their sanitation needs, but limited research has focused specifically on this issue. Qualitative and quantitative data were collected from women in the Mathare informal settlement in Nairobi, Kenya in 2016. A latent class an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…However, in the present study, most isolates were retrieved from male patients in the age group 12–45 years (30/34, 88.2% of isolates), similar to reports by another study in Iran [ 41 ]. The affected age group and gender are important for the epidemiology of shigellosis infections and appeared to be associated with the level of personal hygiene [ 42 ]. It has been suggested that females appeared to maintain better personal hygiene than males, as reported by Mayavati.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the present study, most isolates were retrieved from male patients in the age group 12–45 years (30/34, 88.2% of isolates), similar to reports by another study in Iran [ 41 ]. The affected age group and gender are important for the epidemiology of shigellosis infections and appeared to be associated with the level of personal hygiene [ 42 ]. It has been suggested that females appeared to maintain better personal hygiene than males, as reported by Mayavati.…”
Section: Discussionmentioning
confidence: 99%
“…As more sanitation interventions are being introduced into settlements, women’s regular access to toilets is expanding. For example, findings from this study suggest about 40% of women report having access to a toilet at all times during the night and day, up from only 26% in 2016 [18]. Even the most recent evidence, however, suggests that well over half of women do not have access to a toilet at all times.…”
Section: Discussionmentioning
confidence: 84%
“…Previous research in Mathare, carried out by the authors of this study, suggests that the majority of women living in these environments cannot, for a variety of reasons including lack of resources and/or time, fear of violence, health concerns, time of day, and building closures, access a toilet for all of their daily sanitation needs and, as a result, revert at least once in a 24 h period to using open defecation and/or plastic bags or buckets in their homes (which are then emptied into open drainages outside the home) to manage urination and/or defecation [18,33,34,35]. As more sanitation interventions are being introduced into settlements, women’s regular access to toilets is expanding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While transmission of COVID-19 in the country remains low [1], the potential for uncontrolled outbreaks in urban slums is still of great concern given that 60-70% of Nairobi residents reside in informal settlements [2]. To prevent COVID-19, the World Health Organization has promoted physical distancing (e.g., keeping 1-2 m apart, avoiding touching) and handwashing [1], but these strategies are harder to implement in informal settlements, areas that are densely populated, overcrowded, lack access to running water or improved sanitation, are comprised of multigenerational households, have transient household members, and experience pervasive poverty with many households having unstable or informal income [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%